METODE SERVQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) DALAM MENGUKUR KEPUASAN KONSUMEN TERHADAP LAYANAN DI HYGGE SOCIAL CAFE PASCA PANDEMI COVID-19 - Putu Steven Eka Putra; Eko Sulistyo; IWK.Teja Sukmana (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
Measuring service quality is essential for restaurants. This study determines the quality of service and service attributes that need attention at Hygge Social Café. The research was conducted using the Important Performance Analysis and servequal methods. The sample was thirty people who were taken randomly from Hygge Social Cafe customers. The results showed that the Service Gap has an average of -0.02 with an average service quality value (Q) of 0.995, this indicates that the quality of service has not met consumer expectations adequately, furthermore by the Importance Performance Analysis (IPA) based on the dimension of the level of satisfaction and the level of expectations, data is obtained in quadrant A there were 4 attributes, quadrant B were 6 attributes, quadrant C were 7 attributes and quadrant D were 6 attributes. Notably the four existing quadrants, it is recommended that Hygge Social Café pay attention to quadrant A with 4 existing attributes.